Business Model Canvas for Innovation of Farmer Business Institutions as a Capital Buffer for Corn Farming in Muna Regency - Gogor Arif Handiwibowo (Fakultas Ekonomi Universitas Kadiri, 2026)
Muna Regency is a regency in Southeast Sulawesi Province whose economy relies heavily on agriculture. Corn is one of the main commodities of Muna Regency. One of the phenomena faced by farmers is the lack of working capital for farming. The Muna Regency Agriculture Office initiated the formation of a business institution in the form of a cooperative that functions primarily as a savings and loan institution. Farmers throughout Muna Regency become members of the cooperative and receive priority for capital loans. This proposal is certainly an innovation from the agriculture office to improve the standard of living of farmers. Of course, this institution is expected to channel working capital to farmers in Muna Regency. To form a reliable cooperative, a BMC (Business Model Canvas) study is needed to run it as an independent and sustainable cooperative.